1977
DOI: 10.1111/j.1469-8137.1977.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

SULPHUR DIOXIDE METABOLISM IN SOY‐BEAN, GLYCINE MAX VAR. BILOXI

Abstract: SUMMARY First‐trifoliate leaves of four‐leaved soybean plants were exposed to 35SO2 in the light or dark, and the uptake and translocation of radioactivity measured. Nearly four times more 35SO2 was taken up in the light (stomata open) than in the dark (stomata closed) but approximately 50% of the radioactivity was leached from the leaf surface in the dark compared with 5% in the light. A greater proportion of the source‐leaf radioactivity was translocated in the dark but, in absolute terms, the quantity of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
4

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 8 publications
3
7
0
4
Order By: Relevance
“…A aplicação foliar de 35 S resultou em pronta absorção e rápida translocação do radioisótopo para todas as partes da planta (Tabela 3). Resultados semelhantes foram obtidos por Garsed & Read (1977a, 1977b ao aplicarem 35 SO 2 à primeira folha trifoliada de plantas de soja.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A aplicação foliar de 35 S resultou em pronta absorção e rápida translocação do radioisótopo para todas as partes da planta (Tabela 3). Resultados semelhantes foram obtidos por Garsed & Read (1977a, 1977b ao aplicarem 35 SO 2 à primeira folha trifoliada de plantas de soja.…”
Section: Resultsunclassified
“…Dessa for- B A ma, uma fração em torno de 98% do 35 S foi mantida nas folhas de milho e de soja tratadas com a solução marcada (Tabela 3). Resultados semelhantes foram obtidos por Garsed & Read (1977a).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…How do we unravel the role of plant SO? Previous data showed that plants subjected to sulfur-labeled SO 2 gas readily converted the radioactive label into sulfate (12,13), yet the corresponding enzyme catalyzing this reaction was not characterized at that time. Most importantly, this reaction was interpreted as the key step ("safety valve") in protecting plants from acid rain that has been one major cause of forest damage (14).…”
mentioning
confidence: 99%
“…1). The stimulation of sulphate uptake by light and its inhibition by darkness or sulphite preincubation indicates that the process is probably energydependent (Garsed & Read, 1977).…”
Section: Experimental Conditionsmentioning
confidence: 99%